Glutathionylated 4-hydroxy-2-(E)-alkenal enantiomers in rat organs and its contributions towards the disposal of 4-hydroxy-2-(E)-nonenal in rat liver - Sadhukhan, Sushabhan (2014)
The major route for elimination of 4-hydroxy-2-(E)-nonenal (4-HNE) has long been considered to be through glutathionylation and eventual excretion as a mercapturic acid conjugate. To better quantitate the glutathionylation process, we developed a sensitive LC-MS/MS method for the detection of glutathione (GSH) conjugates of 4-hydroxy-2-(E)-alkenal enantiomers having carbon skeleton of C-5 to C-12. The newly developed method enabled us to quantify 4-hydroxy-2-(E)-alkenal-glutathione diastereomers in various organs, i.e. liver, heart and brain. We identified the addition of iodoacetic acid as a critical step during sample preparation to avoid an overestimation of glutathione-alkenal conjugation. Specifically, we found that in the absence of a quenching step reduced GSH and 4-hydroxy-2-(E)-alkenals react very rapidly during the extraction and concentration steps of sample preparation. Rat liver perfused with d(11)-4-hydroxy-2-(E)-nonenal (d(11)-4-HNE) revealed enantioselective conjugation with GSH and transportation out of the liver. In the d(11)-4-HNE perfused rat livers, the amount of d(11)-(S)-4-HNE-GSH released from the rat liver is higher than the d(11)-(R)-4-HNE-GSH, and more d(11)-(R)-4-HNE-GSH than d(11)-(S)-4-HNE-GSH remained in the perfused liver tissues. Overall, the glutathionylation pathway was found to account for only 8.7% of the disposition of 4-HNE, whereas catabolism to acetyl-CoA, propionyl-CoA, and formate represented the major detoxification pathway.